Hindi as an object of language policy of independent India (Journal of Oriental Studies, 2016)
This article is devoted to language situation and actual problems of  language policy of India after the gaining an Independence. Of regularly in this article mentioned the status of the national language and problems of official languages, language of rulers, local languages. In this article considered the status of national language.
Keywords: State language; language situation; оfficial languages of states; Indian languages; hindi language and English